Influence of boron incorporated biphasic calcium phosphate on mechanical, thermal, and biological properties of poly(vinylidene fluoride) membrane scaffold - Mutlu, Buesra; Demirci, Fatma; Duman, Seyma (Wiley, 2024)
In this paper, boron (B)-doped biphasic calcium phosphate (BCP)/poly(vinylidene fluoride) (PVDF) membrane scaffolds were developed by the combination of non-solvent induced phase separation and lyophilization processes. In addition, the effects of the synthesized B-incorporated BCP powders on the properties of the fabricated scaffolds were investigated. The physicochemical and morphological properties of the scaffolds were characterized by Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy. The physical properties were evaluated by surface wettability and swelling measurements, whereas the mechanical properties were investigated by tensile strength measurements. The thermal behavior was determined by differential scanning calorimetry, the beta-crystallization ratio was calculated by FTIR, and the beta-phase structure was characterized by X-ray diffraction. The bioactivity was evaluated in the simulated body fluid, and the cytotoxicity of the scaffolds was also investigated by performing in vitro cell culture experiments. The results showed that the incorporation of B into the PVDF matrix improved the hydrophilicity while reducing the degree of swelling of the scaffolds. Tensile strength was slightly reduced by the powder content, but yet the strength of all scaffolds was mechanically compatible with native bone. Increasing the B content up to 0.5 and 1 wt.% was improved the thermal properties, the beta-crystalline phase fraction, and thus the piezoelectricity. Furthermore, B-doped BCP/PVDF-based scaffolds significantly promoted bioactivity, cell viability, and proliferation without cytotoxicity, compared to the PVDF scaffold, depending on the B content. In conclusion, our results indicate that the PVDF-based composites in the form of membrane scaffolds that support bone growth have the potential to be highly sought-after candidates in the field of biomedical applications.
Keywords: biphasic calcium phosphate; bone tissue engineering; boron; membrane scaffold; phase seperation; poly(vinylidene fluoride)